2021
DOI: 10.1101/2021.09.17.21263582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socially stratified DNA-methylation profiles are associated with disparities in child and adolescent mental health

Abstract: Importance: Economic and racial inequality is linked to disparities in children's mental health. Biomarkers that reflect these social disparities are lacking. Objective: We examined the hypothesis that salivary DNA-methylation patterns of higher inflammation and faster pace of biological aging are economically, racially and ethnically stratified and are associated with child mental health. Design: The Texas Twin Project is an on-going, observational, longitudinal study that began in May 2012. Analyses were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…First, the sample was relatively homogeneous regarding socio‐economic and ethnic background and included mostly Dutch families of middle‐ to higher‐SES. Our results might not replicate or might emerge even stronger in more varied samples including participants from lower SES strata, and/or ethnic minorities (Raffington, Tanksley, Vinnik, et al., 2021). Second, although we used contemporary algorithms for the most commonly used epigenetic clocks, the field is rapidly moving forward and newer adjustments such as clocks trained in specific (younger) populations may be a way to improve in the future (Dammering et al., 2021; McEwen et al., 2020).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…First, the sample was relatively homogeneous regarding socio‐economic and ethnic background and included mostly Dutch families of middle‐ to higher‐SES. Our results might not replicate or might emerge even stronger in more varied samples including participants from lower SES strata, and/or ethnic minorities (Raffington, Tanksley, Vinnik, et al., 2021). Second, although we used contemporary algorithms for the most commonly used epigenetic clocks, the field is rapidly moving forward and newer adjustments such as clocks trained in specific (younger) populations may be a way to improve in the future (Dammering et al., 2021; McEwen et al., 2020).…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have found links between externalizing symptoms and DNAm (Barker, Walton, & Cecil, 2018; Carpentieri et al., 2021; Cicchetti & Handley, 2017). However, the only study we located that examined the links between externalizing symptoms and EA found a positive link with inflammation‐related methylation profiles, but not with epigenetic age (Raffington, Tanksley, Vinnik, et al., 2021). Thus, to the best of our knowledge, this is the first study showing the potential effects of preceding externalizing problems on EA.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, evidence underscores the concept that DNA methylation functions as a lifelong mechanism for genome adaptation [ 2 ]. Additionally, studies have illuminated that DNA methylation profiles and psychiatric symptoms in children differ based on socioeconomic conditions, race, and ethnicity [ 3–5 ]. A correlation has been observed where increased symptomatology reports are associated with higher salivary DNA methylation profiles indicating greater inflammation and accelerated biological ageing [ 6 ].…”
Section: Introductionmentioning
confidence: 99%